2019
DOI: 10.1016/j.foodqual.2018.08.012
|View full text |Cite
|
Sign up to set email alerts
|

We will eat disgusting foods together – Evidence of the normative basis of Western entomophagy-disgust from an insect tasting

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 60 publications
6
111
0
3
Order By: Relevance
“…Accordingly, younger males with a weak attachment to meat, who are more open to trying novel foods, and who are interested in the environmental impact of their food choices are more likely to become early adopters of edible insects. Other results addressing situational factors of insect-consumption point to effects of insect processing (i.e., insect visibility, Hartmann et al, 2015;Jensen and Lieberoth, 2019), advertising content (e.g., hedonic framing, Berger et al, 2018) and cultural variation (Tan et al, 2015). Finally, previous research suggests that one main reason for individuals' aversion toward insect-based foods lies in the disgust they evoke (Hartmann and Siegrist, 2016;La Barbera et al, 2018;Berger et al, 2019), which allegedly results from Westerners' association of insects with decaying matter and feces (Looy et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Accordingly, younger males with a weak attachment to meat, who are more open to trying novel foods, and who are interested in the environmental impact of their food choices are more likely to become early adopters of edible insects. Other results addressing situational factors of insect-consumption point to effects of insect processing (i.e., insect visibility, Hartmann et al, 2015;Jensen and Lieberoth, 2019), advertising content (e.g., hedonic framing, Berger et al, 2018) and cultural variation (Tan et al, 2015). Finally, previous research suggests that one main reason for individuals' aversion toward insect-based foods lies in the disgust they evoke (Hartmann and Siegrist, 2016;La Barbera et al, 2018;Berger et al, 2019), which allegedly results from Westerners' association of insects with decaying matter and feces (Looy et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
“…Notably, recent studies have also shown that the influence of social norms on food-related behaviors also translates into the context of entomophagy. Jensen and Lieberoth (2019), for example, found that subjective insect eating norms significantly predicted individuals' tasting behavior of food products containing visible as well as invisible mealworms. In the study of Berger et al (2019), individuals were exposed to different peer and expert ratings about mealworm-based food products.…”
Section: Introductionmentioning
confidence: 99%
“…But given the contrasting results between surveys, with course students associating the preferred brownie with the insect product, taste alone did not seem to be a restricting barrier. Overcoming barriers linked to societal ( Schlup and Brunner 2018 , Jensen and Lieberoth 2019 ) or taste perception ( Sogari et al 2017 ) can play major roles toward eventual acceptance. While delivery of insect products through culturally or gastronomically acceptable products does increase willingness of the customer, our results suggest that interpretation of taste and preference related to cricket powder brownies can be highly subjective.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, entomophagy has been embraced by many cultures and over 1,900 species of insects provide valuable nutrients to people’s diets ( van Huis et al 2013 , Halloran et al 2018 , Kim et al 2019 ). However, insect consumption is less common in many countries in the northern hemisphere, including the United States and most of Europe, where perceived social norms play an important role in dictating whether people will consume insects ( Jensen and Lieberoth 2019 ). A major hurdle in getting people to consume insect products is getting them over the neophobia associated with the initial discomfort often felt when trying something new, such as consuming insect products ( La Barbera et al 2018 , Schlup and Brunner 2018 ).…”
mentioning
confidence: 99%
“…In addition to farming insects and using them raw as food or feed, opportunities abound in processing them into finished goods. Although in Africa insect eating has long been culturally accepted but in the western world the idea is still new with low acceptability and willingness to eat insect (Francesco et al 2017;Niels and Lieberoth, 2018). Likewise in some urban areas in Africa, acceptability of edible insect is quite low, maybe due to urbanization, educational level and perception issues.…”
Section: Edible Insect Product Developmentmentioning
confidence: 99%